2020
DOI: 10.7150/jca.40171
|View full text |Cite
|
Sign up to set email alerts
|

ALDH3A1 acts as a prognostic biomarker and inhibits the epithelial mesenchymal transition of oral squamous cell carcinoma through IL-6/STAT3 signaling pathway

Abstract: Objectives: Aldehyde dehydrogenase 3A1 (ALDH3A1) is a member of the ALDH superfamily and its relationship with oral squamous cell carcinoma (OSCC) still unknown. In our subject, we aimed to reveal the expression pattern and clinical value of ALDH3A1 in OSCC and its biological function in OSCC cell lines. Materials and methods: The expression level of ALDH3A1 in paired OSCC tissues and adjacent noncancerous tissues were detected by quantitative real-time PCR, Western blot and immunohistochemistry. The relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 43 publications
3
28
1
Order By: Relevance
“…To identify the molecular mechanism of ALDH3A1 in LUAD patients, we observed that p53 regulated by ALDH3A1 could influence BAG1 expression that was reported for the first time. A study reported another mechanism that IL-6/STAT3 pathway could be activated through ALDH3A1, contributing to reduced cell proliferation, migration, and invasion in oral squamous cell carcinoma [28], which was in consistent with our findings. However, several studies confirmed that ALDH3A1 was positively associated with tumor cells' progression, which was found in our research [29][30][31][32].…”
Section: Discussionsupporting
confidence: 93%
“…To identify the molecular mechanism of ALDH3A1 in LUAD patients, we observed that p53 regulated by ALDH3A1 could influence BAG1 expression that was reported for the first time. A study reported another mechanism that IL-6/STAT3 pathway could be activated through ALDH3A1, contributing to reduced cell proliferation, migration, and invasion in oral squamous cell carcinoma [28], which was in consistent with our findings. However, several studies confirmed that ALDH3A1 was positively associated with tumor cells' progression, which was found in our research [29][30][31][32].…”
Section: Discussionsupporting
confidence: 93%
“…STAT3 transduces signals from the cell membrane receptors to the nucleus, where it acts as a transcription factor. STAT3 is known to be constitutively activated in various types of cancer (9), such as cutaneous melanoma (10), squamous cell carcinoma (11) and oral squamous cell carcinoma (12). In addition to promoting angiogenesis, STAT3 regulates cell proliferation, migration and invasion of tumor cells, indicating its crucial role in the control of tumor growth and metastasis (10,(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Signal transducer and activator of transcription 3 (STAT3) is a latent cytoplasmic transcription factor, originally discovered as a transducer of signals from cell surface receptors to the nucleus (9). Numerous evidences suggest that STAT3 is constitutively activated in various types of cancer and serve a crucial role in tumor growth and metastasis (9)(10)(11)(12). In addition, STAT3 regulates cellular proliferation, invasion, migration and angiogenesis, which are essential for cancer metastasis (13).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and in vivo experiments showed that UICC could facilitate the expression of IL-6 by combining with its promoter and directly interact with the phospho-STAT3 to improve its protein stability, thus promoting tumor growth and metastasis ( 90 ). There have been some studies showing that the IL-6/STAT3 signaling pathway plays an important role in the metastasis of OSCC ( 91 , 92 ), but there is no research involving the role of lncRNAs in this process.…”
Section: Overview Of Lncrnas Involved In Oscc Metastasismentioning
confidence: 99%